Evaluating and Enhancing On-Site Service Processes: A Path to Improved Customer Satisfaction A Case Study at a Manufacturing Company - Lundgren, Marcus; Nordborg, Martin (My University, 2024)
After-sales services play a crucial role in shaping perceived value for customers and influencing their relationship with the company. On-site services (hereafter OSS) are a part of after-sales service and are performed at the customer’s location upon their request. OSS requires the physical presence of a service provider at the customer's site, enabling a more immediate and customized solution to their specific needs and challenges, often leading to a more personalized service experience. However, satisfying customers often demands higher standards from the service provider. This thesis examines how an OSS process, with multiple actors and stakeholders, can be evaluated and improved to enhance customer satisfaction while maintaining a strong brand image. By integrating theories of value co-creation and service quality, it examines how multiple stakeholders contribute to the service delivery process. The study employed a mixed-methods approach involving surveys, interviews, and focus groups to gather insights from various actors within the service ecosystem. Key findings suggest that service quality, particularly in the dimensions of reliability, responsiveness, and empathy, critically influences customer satisfaction. The research introduces a novel conceptual framework that maps the interactions and value creation in OSS processes, providing a structured approach to understanding and improving customer experiences. This framework aids in pinpointing critical service elements that significantly impact customer perceptions and satisfaction levels. Managerial implications highlight the importance of strategic communication and effective service recovery to maintain a strong brand image and customer loyalty. Future research directions are proposed to further refine the service model and extend its applicability across different industrial contexts.
Keywords: On-site service; Service ecosystem; Customer journey; Customer touchpoint; Outsourced touchpoints; Brand image; Co-creation; Customer satisfaction